Differences in the effectiveness of adding Bobath Exercise with (task-oriented training) on the balance of children with Cerebral Palsy - Anwar, Suharto; Leksonowati, Sri Saadiyah; Suriani, Suriani; Rustianto, Dwi (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to analyze the addition of bobath exercise with (task-oriented training) on the balance of Cerebral Palsy children. Research use method Quasi experiment with pre test – post test two group design involving 44 (66.67%) boys and 22 (33.33%) girls aged 1-7 years. The research subjects were 66 people divided into two groups randomly. Group I, 33 children with cerebral palsy, were given Pilates exercises and group II, 33 children with cerebral palsy, were given bobath exercises. Treat each child with a dose of 1 time/day, 3 times a week with a treatment time of 45 minutes for each child for 16 weeks. Held from January to May 2024 at the Disabled Children's Education Foundation in Makassar City and the Children's Growth and Development Clinic in Daya Makassar City. Result, in the Bobath group's paired t-test statistical test for balance, the value was obtained at p=0.002 and for standing balance, the value was obtained at p=0.083. The bobath exercises group for sitting balance obtained a value of p = 0.001 and for standing balance obtained a value of p = 0.023. The Independent t-test statistical test obtained a value of p = 0.039 for sitting balance and standing balance obtained a value of p = 0.034. Conclusion, Bobath exercises which add task-oriented training to the sitting balance of children with cerebral palsy are effective in improving the sitting balance of children with cerebral palsy.